Effect of geometric size reduction on the thermal efficiency of a galvanized plate biomass stove - Hadi Santoso; Muhammad Azhar; Melda Melda; Marhadi Budi Waluyo; Muh. Firdan Nurdin; Sudirman Sudirman; Shinta Tri Kismanti; Deny Murdianto (Politeknik Negeri Lhokseumawe, 2026)
Improving the thermal efficiency of biomass cookstoves remains essential for enhancing energy utilization and reducing fuel consumption in household applications. This study investigates the effect of geometric size reduction on the thermal performance of a galvanized steel biomass stove equipped with a 12 V DC blower. The original biomass stove constructed from galvanized steel plates with dimensions of 50 × 50 × 55 cm³ equipped with a 12 V DC blower was developed in 2022. Due to its relatively large size, the air–fuel mixture delivered to the combustion chamber was not fully optimized, resulting in a thermal efficiency of only 10%. To address this limitation, the stove dimensions were reduced to 40 × 40 × 40 cm³. The performance evaluation was conducted using the Water Boiling Test (WBT) method with two water volumes (2 L and 5 L) and three fuel masses (40%, 60%, and 80%). The results indicate that reducing the stove dimensions contributes to a significant improvement in thermal efficiency, reaching up to 14.6%.